PENERAPAN METODE K-NEAREST NEIGHBOR PADA PENENTUAN GRADE DEALER SEPEDA MOTOR - Henny Leidiyana (LPPM Nusa Mandiri, 2017)
The mutually beneficial cooperation is a very important thing for leasing and dealer. Incentives for marketing is given in order to get consumers as much as possible. But sometimes the surveyor objectivity is lost due to the conspiracy on the field of marketing and surveyors. To overcome this, leasing a variety of ways one of them is doing ranking against the dealer. In this study the application of the k-Nearest Neighbor method and Euclidean distance measurement to determine the grade dealer. From the test results obtained by the value of accuracy of 64.03%.